Incidence, risk factors and outcomes of Acute Kidney Injury in Chronic Obstructive Pulmonary Disease patients with Acute exacerbation - Regmi, Gunjan; Khanal, Kanak; Arjyal, Batsalya; Pyakurel, Kumud; Shah, Vibek Prabhat; Shahi, Rejina (Nepalese Respiratory Journal, 2023)
Background: There is little data on the incidence, risk factors and outcomes of the AKI among COPD patients who are admitted to critical care units with exacerbation of symptoms. This observational study was conducted to evaluate the incidence and outcome of AKI with AECOPD. Method: We performed an observational study of patients who were admitted in the intensive care unit from August 2021 to February 2023 for acute exacerbation of COPD. Results: During the study period, a total of 108 patients were admitted to the ICU with acute respiratory failure attributed to COPD exacerbation. AKI occurred in 49 patients (45.4%). Independent risk factors for AKI in patients with AECOPD were advanced age, coronary artery disease, anemia, acute respiratory failure, and mechanical ventilation. Patients with AKI had worse prognostic implications and were more likely to require mechanical ventilation (42.8% vs 22.03%, P<0.05), had a longer ICU stay (6 ±1.3 days vs 5.41±1.1 days, P<0.05) and longer hospitalization (7.65±1.42 days vs 6.9±1.2 days, P<0.05); and higher in-hospital mortality (28.5 % vs 11.8 %, P<0.05) than those without AKI. Compared to patients without AKI who had in-hospital mortality rate of 11.8%, those with stage 2, or 3 AKI had rates of 41.6% and 85.7% respectively, that is 2.1- fold and 6.0-fold increased risk of in-hospital death, respectively. Conclusion: Incidence of AKI is relatively high in patient with AECOPD requiring intensive care. Patient with AKI had poor outcomes compared to non-AKI patient with AECOPD. AKI can be a prognostic factor for determining patient survival.